Flow analysis of airfoil with mechanical slat and flap using CFD - Md Daud, Nazri; Sudin, Mohd Nizam; Zakaria, Mohd Shukri (Penerbit Universiti Teknikal Malaysia Melaka, 2022)
The usage of slats and flaps in airfoils may reduce the fuel consumption of airplanes and improve their performance as well. In terms of performance, it will increase the lift coefficient of the airfoil. Therefore, in this study, simulation works have been carried out to investigate the effect of various angles of flap and slat on the lift coefficient of the airfoil. The mechanical slats and flaps are designed to improve the lift coefficient of the airfoil model NACA 0015 at the high angle of attack, α= 17°. While, the angles of flap, β and slat, δ were set at 3 cases, namely (δ = 15°, β = 25°), (δ = 20°, β = 30°) and (δ = 25°, β = 35°). The simulation was performed using Ansys Fluent software. The simulation results of lift coefficient and velocity distribution around the airfoil have been compared between base case and mechanical slat and flap cases. There was about 49% to 110% improvement of lift coefficient by using mechanical slat and flap. In addition, the airfoil with a mechanical slat and flap for the case (δ = 20°, β = 30°) indicates the maximum lift coefficient at 0.3107. The result of the lift coefficient is supported by the result of velocity distribution.